1983
DOI: 10.1007/bf00427563
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in kinetics and side-effects of viloxazine in man and their clinical implications

Abstract: Dose kinetics and side effects of viloxazine (VLX) in 16 healthy volunteers (range age 25-90 years) were studied after single oral administration of 200 mg of VLX. Significant differences in peak plasma values (P less than 0.01), t1/2 (P less than 0.01) and Cl/F (P less than 0.05) were found between subjects under 50 and over 60 years. Positive correlations were found between age and peak plasma values (P less than 0.05), age and AUC (P less than 0.01). No correlations were found between age, t1/2 and Cl/F, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

1983
1983
1993
1993

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…Our results after oral dosing in normal and epileptic subjects clearly indicate that the drug is rapidly absorbed and has a short elimination half-life. These data are in good agreement with those described by Bayiiss and and Vandel et al (1982) but contrast with the results reported by Altamura et al (1983), who found much higher plasma levels and longer elimination half-lives following administration of a single oral 200 mg dose of VLX in young and, especially, elderly subjects. The kinetic profile of VLX after intravenous administration had not been characterized before and therefore information on important kinetic parameters such as clearance, volume of distribution and absolute bioavailability had been lacking.…”
Section: Resultscontrasting
confidence: 55%
“…Our results after oral dosing in normal and epileptic subjects clearly indicate that the drug is rapidly absorbed and has a short elimination half-life. These data are in good agreement with those described by Bayiiss and and Vandel et al (1982) but contrast with the results reported by Altamura et al (1983), who found much higher plasma levels and longer elimination half-lives following administration of a single oral 200 mg dose of VLX in young and, especially, elderly subjects. The kinetic profile of VLX after intravenous administration had not been characterized before and therefore information on important kinetic parameters such as clearance, volume of distribution and absolute bioavailability had been lacking.…”
Section: Resultscontrasting
confidence: 55%
“…A similar finding has been found by us in an acute kinetic study with viloxazine, where the total scores of the side effects were significantly higher in younger subjects, although viloxazine plasma levels were lower (Altamura et al, 1983). These observations have some practical implications that support the use of drugs like mianserin and viloxazine for the treatment of involutional melancholia and depressed geriatric patients (Altamura et al, 1982b;Nair & Schwarz, 1982).…”
Section: Mianserin Metabolitessupporting
confidence: 77%
“…Moreover, in the elderly because of alterations in pharmacokinetic parameters like bioavailability, distribution and clearance, the steady state plasma concentrations achieved are significantly higher and lower standard daily doses should be used to avoid overdosing phenomena (Gram et al 1978;Altamura et al 1982Altamura et al , 1983Altamura et al , 1986Cazzullo and Altamura 1985).…”
Section: Abstract: Trazodone -Mianserin Amitriptyline -Elderly -Majomentioning
confidence: 99%